Paralogs of Atlantic salmon myoblast determination factor genes are distinctly regulated in proliferating and differentiating myogenic cells - Bower, Neil I.; Johnston, Ian A. (American Journal of Physiology-Regulatory, Integrative and Comparative Physiology, 2010)
The mRNA expression of myogenic regulatory factors, including myoD1 (myoblast determination factor) gene paralogs, and their regulation by amino acids and insulin-like growth factors were investigated in primary cell cultures isolated from fast myotomal muscle of Atlantic salmon (Salmo salar). The cell cycle and S phase were determined as 28.1 and 13.3 h, respectively, at 18°C. Expression of myoD1b and myoD1c peaked at 8 days of culture in the initial proliferation phase and then declined more than sixfold as cells differentiated and was correlated with PCNA (proliferating cell nuclear antigen) expression (R = 0.88, P < 0.0001; R = 0.70, P < 0.0001). In contrast, myoD1a transcripts increased from 2 to 8 days and remained at elevated levels as myotubes were formed. mRNA levels of myoD1c were, on average, 3.1- and 5.7-fold higher than myoD1a and myoD1b, respectively. Depriving cells of amino acids and serum led to a rapid increase in pax7 and a decrease in myoD1c and PCNA expression, indicating a transition to a quiescent state. In contrast, amino acid replacement in starved cells produced significant increases in myoD1c (at 6 h), PCNA (at 12 h), and myoD1b (at 24 h) and decreases in pax7 expression as cells entered the cell cycle. Our results are consistent with temporally distinct patterns of myoD1c and myoD1b expression at the G and S/G phases of the cell cycle. Treatment of starved cells with insulin-like growth factor I or II did not alter expression of the myoD paralogs. It was concluded that, in vitro, amino acids alone are sufficient to stimulate expression of genes regulating myogenesis in myoblasts involving autocrine/paracrine pathways. The differential responses of myoD paralogs during myotube maturation and amino acid treatments suggest that myoD1b and myoD1c are primarily expressed in proliferating cells and myoD1a in differentiating cells, providing evidence for their subfunctionalization following whole genome and local duplications in the Atlantic salmon lineage.